Colorectal cancer with synchronous hepatic metastases: Systematic review of reports comparing synchronous surgery with sequential bowel-first or liver-first approaches. Issue 2 (February 2016) - Baltatzis, M.; Chan, A.K.C.; Jegatheeswaran, S.; Mason, J.M.; Siriwardena, A.K.
Abstract: Background: The management of colorectal cancer with synchronous liver-limited metastases currently lacks randomised trial evidence to inform case selection for any of the bowel-first, liver-first or synchronous surgery routes. We examine the literature to report outcome data from reports utilising all three approaches. Methods: A systematic review was conducted using OvidSP (including Embase, EBM Reviews and MEDLINE databases) to find articles reporting discrete peri-operative and long-term outcomes for patients undergoing sequential bowel-first, liver-first surgery or synchronous liver and bowel surgery. Results: Of 223 unique citations, 3 cohort studies were identified comprising a pooled population of 1203 patients who completed treatment protocols between 1982 and 2011. Patients were allocated to bowel-first surgery (748 patients, 62.2%), liver-first surgery (75, 6.2%) or synchronous liver/bowel surgery (380, 31.6%). Minor complications were similar between procedures. Major complications were consistent with a pooled fixed estimate of 9.1% (95%CI: 7.6%–10.8%, I 2  = 48%). Post-operative death was rare and consistent with a pooled fixed effect estimate of 3.1% (95%CI: 2.2%–4.3%, I 2  = 0%). Median follow-up ranged from 25.1 to 40.0 months, with a pooled underlying 5-year survival fixed effect estimate of 44% (I 2  = 39%). Conclusion: This review assesses outcomes of patients with colorectal cancer with synchronous liver metastases managed by either synchronous, sequential liver-first or bowel-first surgery. Overall treatment-related mortality is low and survival is similar among the three groups. These findings provide support for the continued use of all three pathways until better evidence to guide selection of an individual treatment option is available.